GE_GERICHTE P/1014/2020 vom 19. Januar 2022 - GE Cour de justice (2022)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;INFRACTIONS CONTRE L'HONNEUR;MENACE(DROIT PÉNAL) | CPP.310.al1.letc; CPP.8.al1; CP.52; CP.177; CP.180